An optimized and validated 384-well plate assay to test platelet function in a high-throughput screening format. (4th July 2019) - Martins Lima, Augusto; Bragina, Maiia E.; Burri, Olivier; Bortoli Chapalay, Julien; Costa-Fraga, Fabiana P.; Chambon, Marc; Fraga-Silva, Rodrigo A.; Stergiopulos, Nikolaos
Abstract: Despite significant advances in the treatment of cardiovascular diseases, antiplatelet therapies are still associated with a high risk of hemorrhage. In order to develop new drugs, methods to measure platelet function must be adapted for the high-throughput screening (HTS) format. Currently, all assays capable of assessing platelet function are either expensive, complex, or not validated, which makes them unsuitable for drug discovery. Here, we propose a simple, low-cost, and high-throughput-compatible platelet function assay, validated for the 384-well plate. In the proposed assay, agonist-induced platelet activity was assessed by three different methods: (i) measurement of light absorbance, which decreases with platelet aggregation; (ii) luminescence measurement, based on ATP release from activated platelets and luciferin–luciferase reaction; and (iii) automated bright-field microscopy of the wells and further quantification of platelet image area, described here for the first time. Brightfield imaging results were validated by demonstrating the similarity of dose–response curves obtained with absorbance and luminescence measurements after stimulating platelets, pre-incubated with prostaglandin E1 or tirofiban, and demonstrating the similarity of dose–response curves obtained with agonists. Assay quality was confirmed using the Zʹ-factor, a statistical parameter used to validate the robustness and suitability of an HTS assay. The results showed that, under high rotations per minute (1200 RPM), an acceptable Zʹ-factor score is reached for absorbance measurements (Zʹ-factor – 0.58) and automated brightfield imaging (Zʹ-factor – 0.52), without the need of replicates, while triplicates must be used to achieve an acceptable Zʹ-factor score (0.54) for luminescence measurements. Using low platelet concentration (4 × 10 4 /μl – 10 μl), the brightfield imaging test was further validated using washed platelets. Furthermore, drug screening was performed with compounds selected by structure-based virtual screening. Taken together, this study presents an optimized and validated assay for HTS to be used as a tool for antiplatelet drug discovery.